KAJIAN PEMBERIAN PAKAN ALTERNATIF TERHADAP KONSUMSI, KECERNAAN, DAN EFISIENSI PENGGUNAAN PAKAN PADA JELARANG PAHA PUTIH (RATUFA AFFINIS RAFFLES, 1821) - Farida, Wartika Rosa; Prijono, Siti Nuramaliati (Perhimpunan Biologi Indonesia, 2013)
Four cream-coloured giant squirrel (Ratufa affinis) consisted of one male and three females used in this study to determinethe effect of feeding alternatives on consumption, digestibility, and feed efficiency use. During the studyeach of the animals was placed in individual cages equipped with sleeping box. Feed given were consisting of Guava(Psidium guajava), sweet corn (Zea mays), coconut (Cocos nucifera), peanut (Arachis hypogea), cucumber (Cucumissativus), mung bean sprouts (Vigna radiata), and sunflower seed (Helianthus annuus). Feedstuffs are given based onthis animal preferences on the grain in its natural habitat. Feed given cafetaria and drinking water available ad libitum.Results showed that the average of dry matter consumed by male was 45.95 g / head / day and by female 39.14g / head / day; rough protein by male 6.99 g / head / day and by female 5.76 g / head / day ; gross energy by male2392 cal / head / day and by female 2116 cal / head / day. Feed efficiency use of male is 13,99% and female is12,63%. The average of body weight gain of the male animal is higher than that of the female, namely 6.43 g / head /day and 4.88 g / head / day respectively. The average value of digested organic matter or Total Digestible Nutrient(TDN) was higher in the female animal, namely 95.41%, than that of the male, namely 92.68%; as well as digestedenergy or Digestible Energy (DE) in the female animal was higher than that in the male, namely 93.60% and91.17%, respectively.